CHARACTERIZATION AND IDENTIFICATON OF MINERAL MAGNETIC PHASE ON LAVA PRODUCT OF MOUNT BLAU IN THE IJEN VOLCANIC COMPLEX, BANYUWANGI, EAST JAVA - Faisal Fath, Muhammad
Volcanic research is very closely related to volcanic products in the form of lava. Lava is a volcanic rock that plays quite well as a recorder of the process of magmatism. As for one of the right methods to understand the process of magmatism in volcanoes is to do characterization. In this study, characterization of samples taken from Blau Volcano in Ijen Volcanic Complex, Banyuwangi, East Java. Characterization of lava is done by integrating the rock magnetization method, geochemistry, and MND (Microlite Number Density). The measurements related to the magnetic properties of rocks consist of frequency susceptibility based on frequency, measurements of IRM (Isothermal Remanence Magnetization), ARM (Anhysteretic Remanence Magnetization), VSM (Vibrating sample Magnetization), and thermomagnetic measurements. Meanwhile, geochemical analysis using the XRF (X-ray fluorescence) method. From the results of these measurements, data processing is carried out so that interpretation can be done on each lava product in order to understand more details about the magmatism process. In addition, this research also discusses the reason for the presence of magnetic mineral phases identified in several rock samples. This is known based on the presence of magnetic coercivity components in IRM (Isothermal Remanence Magnetization) measurements and there is more than one Curie point in thermomagnetic measurements. Analysis using the MND method suggests that the presence of more than one magnetic mineral phase is due to the difference in cooling rate during the magma differentiation process. Then the results of the analysis that have been obtained can also be used to make comparisons between Mount Blau samples with samples from Mount Ijen Muda and Mount Anyar where it has been previously known that Mount Blau samples which have a relatively old age compared to other mountains turned out to also have characteristics differ from the two mountains both in terms of abundance of magnetic minerals, types of magnetic minerals, number of phases (components) of magnetic minerals, magnetic grain size of magnetic domain types, and their chemical composition.